BALANCING ADMINISTRATIVE TASKS AND INSTRUCTIONAL LEADERSHIP: BEST PRACTICES FOR INDONESIAN SCHOOL PRINCIPALS - Isny Lellya (Indonesian Journal of Education (INJOE), 2023)
This qualitative study explored the best practices of successful school principals in Indonesia who have been able to balance their administrative tasks with instructional leadership. Purposive sampling was used to select ten school principals from primary and secondary schools in Indonesia with a proven record of balancing their administrative tasks with instructional leadership. Semi-structured interviews were conducted to collect data, which were analyzed using thematic analysis. The findings indicated that successful principals prioritize instructional leadership over administrative tasks, create a positive school culture that supports instructional leadership, and provide ongoing professional development for teachers. The study also identified challenges principals face in balancing their administrative tasks with instructional leadership, such as needing more resources and support. The recommendations for school principals include prioritizing instructional leadership, creating a positive school culture, and providing ongoing professional development for teachers. The study's implications for policy and professional development programs include supporting school principals in balancing administrative and instructional leadership responsibilities. The limitations of the study and directions for future research are also discussed.